Application of Mahalanobis-Taguchi system in ascending case of methadone flexi dispensing (MFlex) program - S. K. M., Saad; S. N. A. M., Zaini; M. Y., Abu (Penerbit UMP, 2021)
Patient under methadone flexi dispensing (MFlex) program is subjected to do methadone dosage trends like ascending case since no parameters have been used to identify the patient who has potential rate of recovery. Consequently, the existing system does not have a stable ecosystem towards classification and optimization due to inaccurate measurement methods and lack of justification of significant parameters which will influence the accuracy of diagnosis. The objective is to apply Mahalanobis-Taguchi system (MTS) in the MFlex program as it has never been done in previous studies. The data is collected at Bandar Pekan clinic with 16 parameters. Two types of MTS methods are used like RT-Method and T-Method for classification and optimization respectively. As a result, RT-Method is able to classify the average Mahalanobis distance (MD) of healthy and unhealthy with 1.0000 and 21387.1249 respectively. Moreover, T-Method is able to evaluate the significant parameters with 10 parameters of positive degree of contribution. 6 unknown samples have been diagnosed using MTS with different number of positive and negative degree of contribution to achieve lower MD. Type 2 of 6 modifications has been selected as the best proposed solution as it shows the lowest positive MD value. In conclusion, a pharmacist from Bandar Pekan clinic has confirmed that MTS is able to solve a problem in classification and optimization of MFlex program.